The Impact of Relationship Marketing and Customer Experience on Consumer Purchase Decisions in the Automotive Sector - Situmorang, Irvan Rolyesh; Gultom, Pesta; Haubu, TJ. (Universitas Pakuan, 2025)
This study aims to examine the influence of relationship marketing and consumer experience on purchase decisions at ACR Diesel, a company engaged in the automotive spare parts industry located in Medan, Indonesia. As competition intensifies in the automotive sector, companies must strengthen long-term customer relationships and deliver positive experiences to maintain market relevance. This research employs a quantitative approach using descriptive and explanatory methods. The study population consisted of 212 customers of ACR Diesel during the 2023 period, with a sample of 139 respondents determined using the Slovin formula with a 95% confidence level. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS software. The findings reveal that both relationship marketing and consumer experience have positive and significant effects, both partially and simultaneously, on purchase decisions. Relationship marketing characterized by trust, commitment, communication, and customer satisfaction plays a crucial role in fostering loyalty and repeat purchases. Similarly, positive consumer experiences in product quality, service responsiveness, and emotional engagement enhance purchasing intentions and decision-making. The study concludes that integrating strong relationship marketing strategies with consistent and satisfying customer experiences can effectively increase consumer purchasing decisions and business sustainability in a highly competitive automotive market.